Manajemen Risiko Reputasi Dalam Pasar Modal Syariah - Sri Rahmani (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
The application of sharia principles in the capital market certainly comes from the Qur'an and the Hadith of the Prophet Muhammad. Both of these sources made the scholars interpret later called the science of jurisprudence. One of the discussions in the science of jurisprudence is a discussion about muamalah, namely the relationship between human beings related to commerce. Based on that Islamic capital market activities are developed on the basis of muamalah fiqh. There are muamalah fiqh rules which state that basically, all forms of muamalah are permissible unless there is an argument which forbids it. This concept is the principle of the Sharia Capital Market in Indonesia. The development of the Sharia Capital Market reached a new milestone with the enactment of Law Number 19 of 2008 concerning Government Sharia Securities on May 7, 2008. This law is needed as a legal basis for the issuance of state sharia securities or state Sukuk. On August 26, 2008, for the first time, the Government of Indonesia issued the State Sharia Securities series IFR0001 and IFR0002.